Fundamentals of Industrial Electronics - Wilamowski, Bogdan M. (CRC Press, 2012)
Fundamentals of Industrial Electronics is the first volume in The Industrial Electronics Handbook, Second Edition. It focuses on the fundamental areas which form the basis for the field of industrial electronics.